Associations of mutually exclusive categories of physical activity and sedentary time with markers of cardiometabolic health in English adults: a cross-sectional analysis of the Health Survey for England. (December 2015) - Bakrania, Kishan; Edwardson, Charlotte; Bodicoat, Danielle; Esliger, Dale; Gill, Jason; Kazi, Aadil; Velayudhan, Latha; Sinclair, Alan; Sattar, Naveed; Biddle, Stuart; Khunti, Kamlesh; Davies, Melanie; et al.
Abstract Background Both physical activity and sedentary behaviour have been individually associated with health, however, the extent to which the combination of these behaviours influence health is less well-known. The aim of this study was to examine the associations of four mutually exclusive categories of objectively measured physical activity and sedentary time on markers of cardiometabolic health in a nationally representative sample of English adults. Methods Using the 2008 Health Survey for England dataset, 2131 participants aged ≥18 years, who provided valid accelerometry data, were included for analysis and grouped into one of four behavioural categories: (1) 'Busy Bees': physically active & low sedentary, (2) 'Sedentary Exercisers': physically active & high sedentary, (3) 'Light Movers': physically inactive & low sedentary, and (4) 'Couch Potatoes': physically inactive & high sedentary. 'Physically active' was defined as accumulating at least 150 min of moderate-to-vigorous physical activity (MVPA) per week. 'Low sedentary' was defined as residing in the lowest quartile of the ratio between the average sedentary time and the average light-intensity physical activity time. Weighted multiple linear regression models, adjusting for measured confounders, investigated the differences in markers of health across the derived behavioural categories. The associations between continuous measures of physical activity and sedentary levels with markers of health were also explored, as well as a number of sensitivity analyses. Results In comparison to 'Couch Potatoes', 'Busy Bees' [body mass index: −1.67 kg/m2 (p < 0.001); waist circumference: −1.17 cm (p = 0.007); glycated haemoglobin: −0.12 % (p = 0.003); HDL-cholesterol: 0.09 mmol/L (p = 0.001)], 'Sedentary Exercisers' [body mass index: −1.64 kg/m2 (p < 0.001); glycated haemoglobin: −0.11 % (p = 0.009); HDL-cholesterol: 0.07 mmol/L (p < 0.001)] and 'Light Movers' [HDL-cholesterol: 0.11 mmol/L (p = 0.004)] had more favourable health markers. The continuous analyses showed consistency with the categorical analyses and the sensitivity analyses indicated robustness and stability. Conclusions In this national sample of English adults, being physically active was associated with a better health profile, even in those with concomitant high sedentary time. Low sedentary time independent of physical activity had a positive association with HDL-cholesterol.